Anticardiolipin, anti-beta2-glycoprotein I, and antinucleosome antibodies in hepatitis C virus infection and mixed cryoglobulinemia. Multivirc Group - Cacoub, P; Musset, L; Amoura, Z; Guilani, P; Chabre, H; Lunel, F; Poynard, T; Opolon, P; Piette, J C (Journal of rheumatology, 1997)
To investigate anticardiolipin antibodies (aCL), anti-beta2-glycoprotein I (anti-beta2GPI), and antinucleosome antibodies in patients with hepatitis C virus (HCV) with or without mixed cryoglobulinemia. aCL can appear in infectious diseases, but are not then associated with thrombotic events. Antibodies directed to beta2GPI, a co-factor of aCL, have been said to be associated with the presence of "autoimmune" aCL. About 50% of cases of essential mixed cryoglobulinemia are associated with HCV infection. High prevalence of autoantibodies directed to nuclear antigens has been found in HCV infection but the prevalence of antibody to nucleosome has not yet been reported. Group 1: 29 patients with chronic HCV infection and mixed cryoglobulinemia. Group 2: 17 patients with chronic HCV infection but without mixed cryoglobulinemia. To analyze the possible effect of mixed cryoglobulinemia itself on aCL production, we also studied 22 patients with essential mixed cryoglobulinemia and no HCV infection (Group 3). In addition, 96 healthy blood donors were used as a control group (Group 4). Mixed cryoglobulinemia was detected by immunofixation. Anti-HCV antibodies were detected by 3rd generation tests, aCL, anti-beta2GPI, and antinucleosorne antibodies were detected by ELISA. In patients with mixed cryoglobulinemia, we also looked for aCL separately in cryoprecipitate and in serum after extraction of mixed cryoglobulins to investigate a possible "capture" of aCL in the cryoprecipitate. IgG aCL were more frequently found in patients with HCV than in controls [9/46 (20%) vs 2/96 (2%); p < 0.001]. The prevalence of aCL was similar in patients with HCV with or without mixed cryoglobulinemia (6/29 vs 3/17; p = NS). No patient with positive aCL had anti-beta2GPI, antinucleosome antibodies, thrombotic events, or thrombocytopenia. IgG aCL were more frequent in patients with mixed cryoglobulinemia, whatever their status for HCV infection, than in subjects without mixed cryoglobulinemia [8/51 (16%) vs 5/113 (4%); p < 0.02]. The prevalence of aCL was similar in patients with type II or type III mixed cryoglobulinemia. When we looked for aCL separately in serum and in cryoprecipitate, we did not find aCL in cryoprecipitate. In patients with HCV, the prevalence of aCL was not different whether patients were treated or not with interferon alpha. IgG aCL are frequently found in patients with HCV regardless of status for mixed cryoglobulinemia. These aCL have the characteristics of infection related aCL: low titer, absence of thrombotic events, and absence of anti-beta2GPI. The high proportion of aCL in patients with mixed cryoglobulinemia compared to those without, and the absence of antinucleosome antibodies, suggest that these aCL may be secondary to endothelial damage induced by mixed cryoglobulinemia or HCV itself, rather than to nonspecific polyclonal lymphocyte activation.